The Curing Characteristics And Mechanical Properties Of Waste Tyre Dust And Waste Tyre Dust Hybrid Filled Natural Rubber Compounds - Omar, Nurul Farhana (2012)
Curing characteristics, tensile properties, fatigue, swelling behaviour and morphology of waste tyre dust (WTD) filled natural rubber (NR) compounds were studied. The properties of WTD filled NR compounds were studied at various filler loading ranging from 0-30 phr. The curing characteristics such as scorch time (t2) and cure time (t90) and maximum torque (MHR) decreased with increasing WTD loading. The mechanical properties such as tensile properties and fatigue life generally decreased with increasing amount of WTD loading. Increment of WTD loading also contributed to decreasing value of rubber-filler interaction,